Popular music and the rise of populism in Europe - Dunkel, Mario 1982- HerausgeberIn; Schiller, Melanie 1981- HerausgeberIn (Music and Politics, 2025)
This book focuses on the role of popular music in the rise of populism in Europe, centring on the music-related processes of sociocultural normalisation and the increasing prevalence of populist discourses in contemporary society. In its innovative combination of approaches drawing from (ethno)musicology, sociology, and political science, as well as media and cultural studies, this book develops a culture-oriented approach to populism. Based on shared research questions, an original theoretical framework and a combination of innovative methodologies that pay attention to the specific socio-historical contexts, taking into account musical material as well as processes of reception, the five chapters in this volume offer detailed analyses of the nexus of popular music and populism in Hungary, Italy, Austria, Sweden and Germany. All of these countries have seen a marked increase in populist parties and discourses over the last years, as well as significant interactions between populism and popular music. This book will be essential reading for those investigating popular music as a crucial aspect in the study of populism as a cultural phenomenon in Europe. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license